1998
DOI: 10.1177/14034948980260011201
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dementia, delirium and psychiatric symptoms in various care settings for the elderly

Abstract: A prevalence study of psychiatric symptoms was performed in parts of a hospital catchment area in Mid-Sweden. In total 717 patients, aged 75 years and above, who were receiving care in an emergency hospital, three nursing homes, five old people's homes and two home medical care districts were included. All patients were examined using the OBS-scale (Organic Brain Syndrome Scale). Anxiety (51%), psychomotor slowing (45%), delirium (44%), depressed mood (41%), irritability (40%) and dementia (33%) were the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 28 publications
1
71
1
4
Order By: Relevance
“…Dementia is prevalent in 42% of older people admitted to general hospital [3] though published prevalence figures range from 5-45% [3][4][5][6][7][8][9][10][11]. Patients with dementia often have difficulty communicating their needs, and in a hospital setting have a high prevalence of delirium (66%) [12], and psychological symptoms in the absence of delirium (depression (34%), anxiety (35%), delusions (11%) and hallucinations (15%)) [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dementia is prevalent in 42% of older people admitted to general hospital [3] though published prevalence figures range from 5-45% [3][4][5][6][7][8][9][10][11]. Patients with dementia often have difficulty communicating their needs, and in a hospital setting have a high prevalence of delirium (66%) [12], and psychological symptoms in the absence of delirium (depression (34%), anxiety (35%), delusions (11%) and hallucinations (15%)) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to describe dementia prevalence, and the symptoms associated with it, in a general hospital setting have involved prospective objective memory screening, and subsequent clinical assessment [3][4][5][6][7][8][9][10][11][12][13]17]. The rigorous screening methods these studies employ may give an accurate account of the hospital prevalence but they potentially overestimate the actual clinical record, that is, the number of patients with a pre-existing diagnosis of dementia identified as such during their hospital stay and the number of symptoms recorded.…”
Section: Introductionmentioning
confidence: 99%
“…The conformity of the scale with the criteria stated in DSM-III, DSM-III-R and DSM-IV (APA, 1980;1987;1994) have been supported by several studies (Berggren et al, 1987;Sandberg et al, 1998;Andersson et al, 2001). The tests and crossevaluations carried out in these studies strongly confirm the reliability of the diagnosis Article for submiss.…”
Section: Evaluation In Relation To Clinical Relevance and Suitabilitymentioning
confidence: 65%
“…A study focusing upon a single item 'depressed mood' in the OBS 2 scale showed strong correlations with the Montgomery-Åsberg Depression Rating Scale (MADRS) (Montgomery and Åsberg, 1979) and The Clinical Global Impression (CGI) Scale (Guy, 1976) (MADRS: r s 0.85, CGI scale: r s 0.88) (Sandberg et al, 1998) (Table 1 and 2).…”
Section: Reliabilitymentioning
confidence: 99%
“…Başka birçok tıbbi durumun da eşlik edebildiği son dönem kanser hastaları üzerinde prospektif olarak yapılan bir çalışmada %32 oranında deliryum gelişmiştir (10). Bakım evlerinde tedavi gören 75 yaşın üzerindeki 717 hastada yapı-lan bir çalışmada, hastalarda deliryum %43,9 ve deliryumla demans birlikteliği %18,8 oranlarında bulunmuştur (11). Geriatri servisinde yatan 225 hasta üzerinde yapılan başka bir çalışmada ise hastaların %18'inin yatış sırasında deliryum tanısı aldığı ve %24'ünde ise yatış sırasında deliryum geliştiği kaydedilmiştir (12).…”
Section: Klinik Ve Araştırma Etkileriunclassified